Active targeting docetaxel-PLA nanoparticles eradicate circulating lung cancer stem-like cells and inhibit liver metastasis - Yang, N; Jiang, Y; Zhang, H; Sun, B; Hou, C; Zheng, J; Liu, Y; Zuo, P (American Chemical Society, 2014)
Lung cancer is the major cause of cancer related lethality worldwide, and metastasis to distant organs is the pivotal cause of death for the vast majority of lung cancer patients. Accumulated evidence indicates that lung cancer stem-like cells (CSLCs) play important roles in metastagenesis, and these circulating CSLCs may be important targets to inhibit the subsequent metastasis. The present study was aimed at establishing CSLC-targeting polylactic acid (PLA) encapsulated docetaxel nanoparticles for antimetastatic therapy. Cyclic binding peptides were screened on CSLCs in vitro and the peptide CVKTPAQSC exhibiting high specific binding ability to pulmonary adenocarcinoma tissue was subsequently conjugated to the nanoparticles loaded with docetaxel (NDTX). Antimetastatic effect of CSLC-targeting nanoparticles loaded with docetaxel (TNDTX) was evaluated in a nude mouse model of liver metastasis. Results showed that, in the absence of targeting peptide, NDTX hardly exhibited any antimetastatic effect. However, TNDTX treatment significantly decreased the metastatic tumor area in the nude mouse liver. Histopathological and serological results also confirmed the antimetastatic efficacy of TNDTX. To our knowledge, this is the first report on establishing a CSLC-based strategy for lung cancer metastatic treatment, and we hope this will offer a potential therapeutic approach for management of metastatic lung cancer.